Financial Management Behavior of Micro-Businesses in Tourism Destinations: A Qualitative Study - Boediman, Alfred; Susanto, Eko; Afgani, Kurnia Fajar; Rahadi, Raden Aswin (Integrasi Sains Media, 2024)
This study explores the financial management behavior of micro-businesses in tourism destinations across West Java, Indonesia. Using a qualitative descriptive approach, data were collected through in-depth interviews and observations of eight micro-entrepreneurs operating in Pangandaran, Lembang, Ciwidey, Ciletuh Geopark, and Puncak. The findings reveal that financial management practices are predominantly informal, with minimal record-keeping, mixing personal and business finances, and reliance on daily cash flow. Low financial literacy, seasonal income fluctuations, and psychological biases such as loss aversion and overconfidence shape these behaviors. Micro-businesses tend to avoid formal financial institutions due to perceived complexity, fear of debt, and limited understanding of financial products, leading to a preference for informal financing sources. The study highlights that these factors weaken financial resilience and hinder business sustainability. Furthermore, limited financial literacy interventions have had minimal impact on changing financial behavior. The research recommends tailored financial literacy programs and access to simplified formal financial services to strengthen micro-business resilience. Addressing knowledge gaps and behavioral tendencies is essential to enhancing financial management practices and supporting micro-enterprises sustainable growth within West Java’s tourism sector.